2011
DOI: 10.1002/acr.20441
|View full text |Cite
|
Sign up to set email alerts
|

Predicting outcomes of lupus nephritis with tubulointerstitial inflammation and scarring

Abstract: Objective In lupus nephritis, glomerular injury correlates poorly with progression to renal failure. While the tubulointerstitium is also commonly involved, the importance of such involvement is not well defined. Therefore, we developed a simple method to assess the prognostic utility of measuring tubulointerstitial inflammation (TI). Methods Sixty-eight SLE patients with lupus nephritis were enrolled. Tubulointerstitial lymphocytic infiltrates were quantitated both by anti-CD45 antibody staining and standar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
245
2
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 268 publications
(268 citation statements)
references
References 42 publications
19
245
2
2
Order By: Relevance
“…A possible explanation could be the improved outcomes in class IV (and class III) with current cytotoxic regimens (1). Also, tubulointerstitial inflammation rather than glomerular pathology may be an important determinant of prognosis, which we did not study (32). However, there may have been a true difference in outcomes that our study may not have detected due to smaller numbers in the nonproliferative classes.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…A possible explanation could be the improved outcomes in class IV (and class III) with current cytotoxic regimens (1). Also, tubulointerstitial inflammation rather than glomerular pathology may be an important determinant of prognosis, which we did not study (32). However, there may have been a true difference in outcomes that our study may not have detected due to smaller numbers in the nonproliferative classes.…”
Section: Discussionmentioning
confidence: 73%
“…Indeed, many studies have found proliferative lesions on biopsy or class IV to have a worse prognosis (2,8,10,30,31). However, there have been some studies that also did not find any differences in outcomes by class of nephritis (11,21,32). A possible explanation could be the improved outcomes in class IV (and class III) with current cytotoxic regimens (1).…”
Section: Discussionmentioning
confidence: 99%
“…The progression of LN from a mild condition to a more severe form and possible renal failure involves multiple pathways within the kidney; therefore, a treatment that targets common underlying pathologies would be advantageous [9,35,36]. Involvement of the TWEAK/Fn14 axis in both glomerular and tubular damage positions this pathway as an attractive therapeutic target for the treatment of patients with LN, many of whom currently rely on broadly immunosuppressive agents [9].…”
Section: Figurementioning
confidence: 99%
“…Baseline assessments were performed prior to dosing on Day 1. Follow-up occurred through the final study visit on Day 71, with assessments on Days 3, 4, 6 (±6 hours), and on Days 8,11,15,22,29,35,43, 57 and 71 (±2 days).…”
Section: Clinical Trial Designmentioning
confidence: 99%
See 1 more Smart Citation